The Broad Clinical Spectrum of Epilepsies Associated With Protocadherin 19 Gene Mutation - Dell'Isola, Giovanni Battista; Vinti, Valerio; Fattorusso, Antonella; Tascini, Giorgia; Mencaroni, Elisabetta; Di Cara, Giuseppe; Striano, Pasquale; Verrotti, Alberto (Frontiers in Neurology, 2022)
Protocadherin 19 (PCDH19) gene is one of the most common gene involved in Epilepsy syndromes. According to literature data PCDH19 is among the 6 genes most involved in genetic epilepsies. PCDH19 is located on chromosome Xq22.1 and is involved in neuronal connections and signal transduction. The most frequent clinical expression of PCDH19 mutation is Epilepsy and Mental Retardation limited to Female (EFMR) characterized by epileptic and non-epileptic symptoms affecting mainly females. However, the phenotypic spectrum of these mutations is considerably variable from genetic epilepsy with febrile seizure plus to Epileptic Encephalopathies. The peculiar exclusive involvement of females seems to be caused by a cellular interference in heterozygosity, however affected mosaic-males have been reported. Seizure types range from focal seizure to generalized tonic-clonic, tonic, atonic, absences and myoclonic jerks. Treatment of PCDH19-related epilepsy is limited by drug resistance and by the absence of specific treatment indications. However, seizures become less severe with adolescence and some patients may even become seizure-free. Non-epileptic symptoms represent the main disabilities of adult patients with PCDH19 mutation. The aim of this review is to analyze the highly variable phenotypic expression of PCDH19 gene mutation associated with epilepsy.